Implementasi Kurikulum Merdeka Belajar Pasca Pembelajaran Daring ‎Di SMKN 2 Cirebon ‎ - Intan Sari ‎; Septi Gumiandari (Indra institute Research & Publication, 2022)
During the Covid-19 pandemic, learning was carried out online (in the network), so after the Covid-19 pandemic, learning was carried out again offline. The 2013 curriculum has changed to become an independent curriculum, namely a curriculum whose learning methods refer to the aptitude and interest approach. Students can choose what subjects they want to learn according to their passion. The purpose of this research is to find out the implementation of the independent curriculum which is carried out in SMKN 2 Cirebon schools. From research at SMKN 2 Cirebon. This study used a qualitative method, data collection was carried out by means of two designs, namely interviews and library research (literature review method). The author found that the concept and application of the independent curriculum went well in accordance with applicable policies and procedures such as providing ATP, TP, and teaching module formats to teachers, and one of the implementations of the independent curriculum for the learning process in class was the use of digital-based.